2017
DOI: 10.1371/journal.ppat.1006476
|View full text |Cite
|
Sign up to set email alerts
|

Innate immunity restricts Citrobacter rodentium A/E pathogenesis initiation to an early window of opportunity

Abstract: Citrobacter rodentium infection is a mouse model for the important human diarrheal infection caused by enteropathogenic E. coli (EPEC). The pathogenesis of both species is very similar and depends on their unique ability to form intimately epithelium-adherent microcolonies, also known as “attachment/effacement” (A/E) lesions. These microcolonies must be dynamic and able to self-renew by continuous re-infection of the rapidly regenerating epithelium. It is unknown whether sustained epithelial A/E lesion pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…Quantitation of cecal luminal lipocalin-2 and histopathology scores both confirmed the protective effects of STm Aux treatment within each mouse genotype ( Supplementary Fig. 11B, C), although these two readouts themselves are MYD88/TRIF-dependent 17,34 and should therefore be compared between both mouse genotypes with caution.…”
Section: Resultsmentioning
confidence: 62%
“…Quantitation of cecal luminal lipocalin-2 and histopathology scores both confirmed the protective effects of STm Aux treatment within each mouse genotype ( Supplementary Fig. 11B, C), although these two readouts themselves are MYD88/TRIF-dependent 17,34 and should therefore be compared between both mouse genotypes with caution.…”
Section: Resultsmentioning
confidence: 62%
“…We set out to investigate whether specific C-terminal CesT tyrosines are important for bacterial intestinal colonization and disease in a natural mouse infection model for A/E pathogenesis. C. rodentium has been widely used by researchers to assess the role of its putative virulence factors in mice, including many aspects of its cognate T3SS and numerous effectors (8, 3841). Importantly C. rodentium cesT null mutants have been shown to be strongly attenuated for mouse intestinal colonization and disease (8).…”
Section: Resultsmentioning
confidence: 99%
“…We did observe that C. rodentium (CesT F152, F153) did replicate within mice, but was cleared from the mouse colon more rapidly than wild type C. rodentium . Recently, it has been demonstrated that the establishment phase of C. rodentium pathogenesis in vivo is restricted to a very short window of opportunity (~18 hours) that determines intestinal intimate attachment and disease severity (41). Indeed, our data directly agree with those findings in that bacteria expressing CesT F152, F153 were attenuated for F-actin pedestal formation (EPEC) and mouse intestinal infection ( C. rodentium ).…”
Section: Discussionmentioning
confidence: 99%
“…Following entry to the body via oral route, C. rodentium colonizes the caecal patch, a type of lymphoid tissue in caecum, from where the bacteria gradually progress to colonise distal colon [17] [18] [19]. For colonization, the bacteria triggers localised damage of brush border microvilli, which mediates bacteria to attach to the epithelial cell surface.…”
Section: Rodentium An Attaching and Effacing Pathogenmentioning
confidence: 99%
“…The only means that are currently available to address this limitation include transgenic strains of C. rodentium that express OVA or GFP [96] [97] [98]. Another probable limitation to study this pathogen could be the loss of antibiotic sensitivity of C. rodentium due to the development of worldwide emergence of multi-resistant strains [19].…”
Section: Limitations Of C Rodentium Modelmentioning
confidence: 99%